Analisis Perbandingan Pembiayaan KPR Menggunakan Akad Murabahah Dengan Akad Musyarakah Mutanaqisah Di Bank Syariah Indonesia KC. Medan Aksara - Melisa Ananda Putri Ritonga (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The aim of this research is to determine the application and comparison of murabahah and musyarakah mutanaqisah contracts in applying for Sharia KPR financing at Bank Syariah Indonesia. The method used in this research is qualitative descriptive research. The information obtained in this research is the result of interviews, observation and documentation. The research results show that the implementation of both contracts begins with a financial request with the same administrative requirements. Comparison of contracts can be seen in similar things, namely. administrative requirements, installment financing, accelerated repayment system and legal consequences for defaulting customers. The differences between these contracts lie in the characteristics of the contract, the definition of margin, the bank's relationship with the customer, the value of the object and home ownership. In its implementation, it can be done by considering the advantages and disadvantages of the two contracts.